Iron metabolism gene expression and prognostic features of hepatocellular carcinoma. Issue 11 (4th August 2018) - Shen, Ying; Li, Xin; Zhao, Bin; Xue, Yanru; Wang, Shenghang; Chen, Xin; Yang, Jiancheng; Lv, Huanhuan; Shang, Peng
Abstract: Iron metabolism is crucial to hepatocellular carcinoma progression and is a key determinant of prognosis. Protein‐protein interactions within the iron metabolism gene network were analyzed using the European Molecular Biology Laboratory's Search Tool for Recurring Instances of Neighbouring Genes/Proteins database. We obtained 423 liver hepatocellular carcinoma gene expression profiles from the Cancer Genome Atlas database. The expression and pathway enrichment of representative iron intake genes ( TFRC and DMT1 ), utilization genes ( FTH1, FTL, HIF1A, HMOX1, SLC25A37, and SLC25A38 ), and efflux genes ( FLVCR1 and SLC40A1 ) was investigated in tumor and adjacent tissues. We determined the relationship between iron metabolism and the prognostic features of liver hepatocellular carcinoma. The liver metabolism genes TFRC and FLVCR1 were related to survival, disease status, and prognosis in patients with hepatocellular carcinoma. Our results provide novel insight into liver cancer therapy. Abstract : As the most important iron storage organ, the carcinogenesis of liver is highly related to iron metabolism. The functions of iron metabolism–related genes are important in liver cancer. Iron metabolism–related genes contribute to liver cancer by multiple pathways.